2019
DOI: 10.3892/mco.2019.1927
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfunctioning thyroid carcinoma: A systematic review

Abstract: Hyperthyroidism may be caused by the development of primary or metastatic thyroid carcinoma. The aim of the present study was to collect recently reported cases of hyperfunctioning thyroid carcinoma in order to analyze its pathological characteristics, diagnostic procedures and treatment strategies. A PubMed () search was performed for studies published between January 1990 and July 2017. Full-text articles were identified using the terms, ‘hyperfunctioning thyroid carcinoma/cancer’, ‘malignant hot/toxic thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 45 publications
2
46
0
2
Order By: Relevance
“…CGRP is generated as an alternative RNA splicing of the CALCA gene encoding calcitonin, CGRP, and catakalcin (procalcitonin). Our group and others [49,50] have confirmed that positivity for CGRP also supports a C cell origin. A subset of unusual calcitonin-negative medullary thyroid carcinomas are characterized by no elevated serum calcitonin levels, no calcitonin expression on immunohistochemistry, and no expression for calcitonin mRNA.…”
Section: Calcitonin-negative Medullary Thyroid Carcinomasupporting
confidence: 84%
See 1 more Smart Citation
“…CGRP is generated as an alternative RNA splicing of the CALCA gene encoding calcitonin, CGRP, and catakalcin (procalcitonin). Our group and others [49,50] have confirmed that positivity for CGRP also supports a C cell origin. A subset of unusual calcitonin-negative medullary thyroid carcinomas are characterized by no elevated serum calcitonin levels, no calcitonin expression on immunohistochemistry, and no expression for calcitonin mRNA.…”
Section: Calcitonin-negative Medullary Thyroid Carcinomasupporting
confidence: 84%
“…3c). Metastatic lesions may also preserve the autonomous production of thyroid hormone [49]. A recent series reported an increased risk of malignancy in TSHR-mutant functional thyroid nodules when TSHR mutations occur at high allelic frequency [50].…”
Section: Functional Follicular Neoplasmsmentioning
confidence: 99%
“…Anders als bei dem hier beschriebenen Patienten handelt es sich bei den Patienten mit heißen Schilddrüsenkarzinomen gerade im Vergleich zu den benignen autonomen Adenomen um meist jüngere weibliche Patienten [ 11 ]. Darüber hinaus weisen die meisten Patienten mit einem Karzinom in einem heißen Knoten Zeichen der Hyperthyreose mit erhöhten T3- (76,5 %) und T4-Werten (51,9 %) bei gleichzeitig supprimiertem TSH auf [ 10 , 11 ]. Diese Daten werfen die Frage nach der Definition eines heißen Schilddrüsenkarzinoms auf.…”
Section: Diskussionunclassified
“…Wie im vorliegenden Fall handelt es sich bei den heißen Schilddrüsenkarzinomen häufig um follikuläre Karzinome, die nach den Daten eines systematischen Reviews bei knapp 47 % der nichtmetastasierten und bei etwa 72 % der metastasierten hyperfunktionellen Karzinomen nachweisbar sind [ 10 ]. Darüber hinaus zeigen etwa 20 % der papillären Schilddrüsenkarzinome in heißen Knoten eine follikuläre Variante [ 10 ]. Die Ursachen für das gehäufte Auftreten follikulärer Karzinome in autonomen Knoten ist bislang unklar, scheint jedoch durchaus ein gewisses Charakteristikum zu sein.…”
Section: Diskussionunclassified
“…The value of the method is greatly underestimated since the detection of so called “hot nodules” enables a relatively certain exclusion of malignancy in these lesions. Only few cases of autonomously hyperfunctioning TN are reported in the literature, especially if hyperthyroidism coexists [ 20 ]. Recently published cases revealed benign histopathology in >95% of hot TN with intermediate cytology results [ 21 ].…”
Section: Introductionmentioning
confidence: 99%